1995
DOI: 10.1055/s-2007-979605
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Psychophysiology in Nootropic Drug Research: Effects of Ginkgo biloba on Event-related Potentials (P300) in Age-associated Memory Impairment

Abstract: Extracts from the leaves of Ginkgo biloba have been suggested to be useful in the treatment of various symptoms of impaired brain functions in advanced age. To elucidate specific mechanisms of the possible clinical benefit, the effects of Ginkgo biloba extract Ginkobene on cognitive information-processing were investigated by means of long-latency auditory event-related potentials. In a double-blind placebo-controlled study, 48 patients (29 women and 19 men) aged between 51 and 79 years with the diagnosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In the present study, changes in P300 latency were 13.6 msec in the placebo group and 1.8 msec in the LCPUFA group, and were significantly different. The difference in changes between groups was 15.4 msec, and was comparable to the effects of various treatments reported previously, such as exercise for 12 months 11 to 23 msec 33 , 120 mg/day of gingko extract for 8 weeks 32 msec 34 , and 240 mg/ day of ARA for 4 weeks 12 msec 14 in healthy elderly participants. These data suggest that the difference in P300 latency in the present study was physiologically meaningful.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, changes in P300 latency were 13.6 msec in the placebo group and 1.8 msec in the LCPUFA group, and were significantly different. The difference in changes between groups was 15.4 msec, and was comparable to the effects of various treatments reported previously, such as exercise for 12 months 11 to 23 msec 33 , 120 mg/day of gingko extract for 8 weeks 32 msec 34 , and 240 mg/ day of ARA for 4 weeks 12 msec 14 in healthy elderly participants. These data suggest that the difference in P300 latency in the present study was physiologically meaningful.…”
Section: Discussionsupporting
confidence: 87%
“…Another possibility is the repeated measurement of P300. It was reported that three times and more measurement of P300 increased the latency in the elderly 34 , although there were several reports that repeated measurement did not influence the latency in young adults 49 51 . In fact, we set the repeated measurement of P300 measurements at the screening, baseline and 4 weeks after the supplementation in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this stability under normal conditions, EEG signals can be very sensitive to variations in alertness (Broughton 1982;Gevins et al 1977;Makeig and Jung 1995;Matousek and Petersen 1983;Oken and Salinsky 1992; Torsvall and Åk-erstedt 1988), and/or the amount of effortful attention exerted during task performance (Gale et al 1978;Galin et al 1978;Gevins et al 1997;Inouye et al 1988;Miyata et al 1990). Because of such characteristics, EEG measures have often been used to help characterize the central effects of alcohol (Cohen et al 1993;Davis et al 1941;Lukas et al 1986), and psychoactive medications (Bruce et al 1986;Hermann 1982;Saletu et al 1994;Schulz et al 1996;Semlitsch et al 1995).…”
Section: Many Common Pharmacological Treatments Have Effects On Cognimentioning
confidence: 99%
“…Despite this stability under normal conditions, EEG signals can be very sensitive to variations in alertness (Broughton 1982;Gevins et al 1977;Makeig and Jung 1995;Matousek and Petersen 1983;Oken and Salinsky 1992; Torsvall and Åk-erstedt 1988), and/or the amount of effortful attention exerted during task performance (Gale et al 1978;Galin et al 1978;Gevins et al 1997;Inouye et al 1988;Miyata et al 1990). Because of such characteristics, EEG measures have often been used to help characterize the central effects of alcohol (Cohen et al 1993;Davis et al 1941;Lukas et al 1986), and psychoactive medications (Bruce et al 1986;Hermann 1982;Saletu et al 1994;Schulz et al 1996;Semlitsch et al 1995).In the context of such research a large number of studies have employed multivariate pattern classification techniques, including both linear discriminant analysis and neural network approaches, in efforts to automatically detect and classify patterns of EEG changes associated with pharmacological interventions. This has included efforts to discriminate the effects of different classes of psychoactive drugs (e.g., stimulants, antidepressants, tranquilizers, and neuroleptics) as an aid in the evaluation of new pharmacological agents (Hermann 1982), to discriminate the effects of different drugs within a class such as different hypnotics used to induce anesthesia (Veselis et al 1993) and different benzodiazepines used to promote sleep (Gevins et al 1988), and to examine dose-response relationships (Haring et al 1994).…”
mentioning
confidence: 99%
“…In healthy elderly P300 amplitude increased in a dose-dependent manner after single oral doses of 150, 300 and 900 mg tenilsetam and after 5 mg codergodcrine mesylate [7]; after 150 mg bifemelane, P300 latency was shortened [8]. In age-associated memory impairment (AAMI), centro-parietal P300 amplitude was en-hanced after 2 weeks' infusion with 250 ml 20% Actovegin ® [9] and P300 latency was shortened after 8 weeks' treatment with a daily oral dose of 120 mg Ginkgo biloba extract [10]. In mildly demented patients, the centroparietal P300 amplitude increased after one treatment intravenously with 0.2 g amantadine sulfate [11] and in mildly to moderately demented patients with probable dementia of Alzheimer's type and with multi-infarct dementia, P300 latency was shortened after 8 weeks' treatment with 2 !…”
Section: Introductionmentioning
confidence: 99%